Severity of citrus tristeza virus isolates from Texas - Herron, C.; Mirkov, T.; Solis-Gracia, N.; Kahlke, C.; Skaria, M.; Graca, J. da (Scientific Societies, 2005)
Citrus tristeza virus (CTV) isolates collected from the Lower Rio Grande Valley in south Texas and east Texas were characterized using citrus indicators and molecular methods. The citrus indicators were Mexican lime (Citrus aurantifolia), sour orange (C. aurantium), sweet orange (C. sinensis) grafted to sour orange, Duncan grapefruit (C. × paradisi), and Madam Vinous sweet orange, with some CTV isolates additionally indexed using the Texas commercial grapefruit cvs. Rio Red and Star Ruby, and Marrs and N-33 sweet orange. Severity ratings used 11 biotype groups or cumulative mean relative indices. Molecular characterization was carried out using poly- and monoclonal antibodies, seven strain-specific probes and single-stranded conformational polymorphism, and all were based on the CTV major coat protein or gene. All Texas CTV isolates produced vein clearing symptoms on inoculated Mexican lime plants. Over half of the CTV isolates tested were placed in biotype groups IX and X (causing decline of sweet orange on sour orange, seedling yellows on sour orange and grapefruit seedlings, and stem pitting of grapefruit or sweet orange), and one isolate was in biotype I (mild).